2011
DOI: 10.1073/pnas.1111488108
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosyl hydride (HNO) replaces dioxygen in nitroxygenase activity of manganese quercetin dioxygenase

Abstract: Quercetin dioxygenase (QDO) catalyzes the oxidation of the flavonol quercetin with dioxygen, cleaving the central heterocyclic ring and releasing CO. The QDO from Bacillus subtilis is unusual in that it has been shown to be active with several divalent metal cofactors such as Fe, Mn, and Co. Previous comparison of the catalytic activities suggest that Mn(II) is the preferred cofactor for this enzyme. We herein report the unprecedented substitution of nitrosyl hydride (HNO) for dioxygen in the activity of Mn-QD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 64 publications
0
23
0
Order By: Relevance
“…On-going studies outside the scope of this review continue to explore HNO’s role in basic cardiac physiology or define HNO’s reactivity with oxygen or new targets, such as cobalt-containing proteins or manganese quercetin dioxygenase. 110,156158 Reactions of HNO with the proteins that control hydrogen peroxide degradation reveals a “cross-talk” between HNO and hydrogen peroxide that may define new redox based signaling or gene expression pathways. 159 The combination of the advances in HNO detection and donation with these emerging areas highlights the enormous potential of these new chemical biology tools to understanding HNO’s actions in biology, physiology and medicine.…”
Section: Resultsmentioning
confidence: 99%
“…On-going studies outside the scope of this review continue to explore HNO’s role in basic cardiac physiology or define HNO’s reactivity with oxygen or new targets, such as cobalt-containing proteins or manganese quercetin dioxygenase. 110,156158 Reactions of HNO with the proteins that control hydrogen peroxide degradation reveals a “cross-talk” between HNO and hydrogen peroxide that may define new redox based signaling or gene expression pathways. 159 The combination of the advances in HNO detection and donation with these emerging areas highlights the enormous potential of these new chemical biology tools to understanding HNO’s actions in biology, physiology and medicine.…”
Section: Resultsmentioning
confidence: 99%
“…As HNO is isoelectronic with O 2 and forms stable diamagnetic adducts with ferrous hemoglobins from various species, we have suggested its use as an O 2 analog [18]. Most recently, we have shown that HNO may replace O 2 during turnover of a non-heme Mn dioxygenase enzyme, quercetin dioxygenase; this nitroxygenase activity results in the regioselective incorporation of the N atom derived from HNO within the enzymatic product [20].…”
Section: Introductionmentioning
confidence: 98%
“…These observations strongly suggest that HNO has significant roles in biology and medicine. It is interesting to note that quite a number of the HNO biological interactions occur with metalloproteins, such as heme proteins [1–3,1518], Cu,Zn-SOD (superoxide dismutase) [19], and manganese quercetin dioxygenase [20]. However, the atomic level structural and functional details of HNO interactions with biological systems are largely unknown.…”
Section: Introductionmentioning
confidence: 99%